Improving the Modelling of Couples' Labour Supply - Cobb-Clark, D; Gong, X; Breunig, R (My University, 2005)
We study the work hours of Australian couples, using a neoclassical labour-supply model in which couples choose from a small, realistic set of possible wife-husband working hour combinations We introduce three improvements to this standard model. First, we allow partners’ preferences about non-market time to be correlated. We also correct the estimates to account for the fact that we estimate the non-observable wage rates of individuals who do not work. Lastly, we allow each individual’s preferences for non-market time to be correlated with her or his wage rate. These changes, which substantially enhance the realism of the standard, discretized labour-supply model, also have an important impact on the results. We estimate the model using HILDA data and find wage elasticities of labour supply – 0.26 for men and 0.50 for women – that are twice as large as those found without these three innovations. Using simulation methods, we then analyze the expected impact of the 2005/06 Australian tax reform. As a result of the tax cuts, we expect working hours to increase by 1.7 per cent for both men and women and household after-tax incomes to increase by approximately $60 per week on average. For families with two wage earners, each earning between $25,000 and $55,000 per year, our model predicts an after-tax increase in income of $38 after accounting for these labour supply effects – much larger than the Australian Government’s own prediction of $12, which does not allow for labour supply effects.
IZA Disxussion Paper
IZA Discussion Papers
Keywords: Employment -- Hours; Employment; Labour market; Employment and unemployment